The puzzle people : memoirs of a transplant surgeon - Starzl, Thomas E. (Thomas Earl), 1926-2017 (University of Pittsburgh Press Digital Editions., 1992)
Given the tensions and demands of medicine, highly successful physicians and surgeons rarely achieve equal success as prose writers. It is truly extraordinary that a major, international pioneer in the controversial field of transplant surgery should have written a spellbinding, and heart-wrenching, autobiography. Thomas Starzl grew up in LeMars, Iowa, the son of a newspaper publisher and a nurse. His father also wrote science fiction and was acquainted with the writer Ray Bradbury. Starzl left the family business to enter Northwestern University Medical School where he earned both an M.D. and a Ph. D. While he was a student, and later during his surgical internship at the Johns Hopkins Hospital, he began the series of animal experiments that led eventually to the world's first transplantation of the human liver in 1963.